2014
DOI: 10.2463/mrms.2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted Imaging of Ovarian Torsion: Usefulness of Apparent Diffusion Coefficient (ADC) Values for the Detection of Hemorrhagic Infarction

Abstract: Purpose: We undertook this study to evaluate the need for diffusion-weighted (DW) magnetic resonance (MR) imaging in detecting hemorrhagic infarction following ovarian torsion.Methods: The study included 14 consecutive patients aged 12 to 74 years (average age, 36 years) with surgical confirmation of ovarian torsion who underwent 1.5-tesla MR imaging. Pathologically, hemorrhagic infarction was found in 7 patients. We retrospectively reviewed signal intensity on T 1 -, T 2 -, and diffusion-weighted images and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 18 publications
3
40
2
Order By: Relevance
“…They found that ADC levels are lower in torsion cases with hemorrhagic infarction compared with patients who do not develop hemorrhagic infarction [14]. Similarly, a preliminary study examined the contribution of DWI in the diagnosis of testicular torsion [21].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They found that ADC levels are lower in torsion cases with hemorrhagic infarction compared with patients who do not develop hemorrhagic infarction [14]. Similarly, a preliminary study examined the contribution of DWI in the diagnosis of testicular torsion [21].…”
Section: Discussionmentioning
confidence: 98%
“…Tissue ischemia results in the deterioration of sodium-potassium pumps, which results from the decrease in ATP levels and the deterioration of the water flow between the extracellular and intracellular areas. DWI provides an obvious contrast between ischemic and normal tissue, and ADC maps obtained from DWI show the limited diffusion numerically [14]. The fact that DWI does not need contrast media makes it more important in the diagnosis of ovarian torsion, especially in pediatric and pregnant patients who have increased incidence of ovarian torsion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…DWI can also increase the conspicuity of a twisted fallopian tube [22]. To our knowledge, no additional diagnostic yield has been demonstrated in diagnosing ovarian torsion by the addition of DWI sequences, but DWI has been shown to be beneficial in identifying hemorrhagic infarction in torsed ovaries where lower ADC values are seen than in ovaries without hemorrhagic infarction [23].…”
Section: Ovarian Torsionmentioning
confidence: 97%
“…It is generally observed in women in the reproductive age group, and it constitutes around 2.7 % of all gynaecological urgent surgical interventions [2,3]. While the conventional treatment method is the extraction of the torsioned ovary, ovarian detorsion must be implemented for patients in whom the protection of fertility is desired.…”
Section: Introductionmentioning
confidence: 99%